2021
DOI: 10.7554/elife.69178
|View full text |Cite
|
Sign up to set email alerts
|

Dorsal premammillary projection to periaqueductal gray controls escape vigor from innate and conditioned threats

Abstract: Escape from threats has paramount importance for survival. However, it is unknown if a single circuit controls escape vigor from innate and conditioned threats. Cholecystokinin (cck)-expressing cells in the hypothalamic dorsal premammillary nucleus (PMd) are necessary for initiating escape from innate threats via a projection to the dorsolateral periaqueductal gray (dlPAG). We now show that in mice PMd-cck cells are activated during escape, but not other defensive behaviors. PMd-cck ensemble activity can also … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 45 publications
2
24
0
1
Order By: Relevance
“…Fear of predators is an aversive emotional state that elicits defensive behaviors such as freezing and escape flight ( Wang et al, 2021a ; Gottfried et al, 2004 ; Clinchy et al, 2013 ). Therefore, we probed the emotional valence of AHN activation in a close loop real-time place avoidance assay (RTPA) ( Figure 2a and b ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Fear of predators is an aversive emotional state that elicits defensive behaviors such as freezing and escape flight ( Wang et al, 2021a ; Gottfried et al, 2004 ; Clinchy et al, 2013 ). Therefore, we probed the emotional valence of AHN activation in a close loop real-time place avoidance assay (RTPA) ( Figure 2a and b ).…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, the same study identified the PMD, not the AHN, as the most responsive hypothalamic region to predatory context despite the relative scarcity of hippocampal innervation in the PMD. Furthermore, a recent study by Wang et al, 2021a found that the PMD activation evokes an organized escape in which mice quickly assess environment’s layout and find efficient flight path, whereas the activation of other hypothalamic nuclei, including the AHN and VMHdm/c, only induced stereotyped panic-related escape responses such as running and jumping ( Wang et al, 2021b ). We found that a direct AHN activation evokes panic-related running and jumping in an empty open field arena with no shelter.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Quantification showed that CCK-GFP cells comprise approximately 5% of l/vlPAG neurons and are more prevalent in the l/vlPAG than dlPAG ( Figure 1C ; n = 4, t (3) = 8.743, p=0.0032). CCK cells in several brain regions such as cortex, hippocampus, and amygdala are reported to be inhibitory ( Kepecs and Fishell, 2014 ; Mascagni and McDonald, 2003 ; Nguyen et al, 2020 ; Whissell et al, 2015 ), though glutamatergic CCK+ cells have also been reported in other regions ( Wang et al, 2021a ). To determine if these cells are glutamatergic, we immunostained against the glutamatergic marker vGlut2 in PAG slices containing GFP-expressing CCK+ cells ( Figure 1D ).…”
Section: Resultsmentioning
confidence: 99%
“…To address this question, we optogenetically activated l/vlPAG-CCK cells while introducing mice to live predator exposure ( Figure 6A ). In this assay, mice are placed in an elongated rectangular arena that contains an awake rat restrained to one end by a harness ( Reis et al, 2021a ; Wang et al, 2021a ; Wang et al, 2021b ). Rats are natural predators of mice, and mice exhibit robust defensive reactions during exposure to a live rat but not a similarly shaped toy rat such as increased freezing, increased distance from the live rat, and reduced time in the zone containing the live rat ( Figure 6B ; n = 10; freezing: t(9) = 3.519, p=0.0065; threat distance: t(9) = 13.09, p<0.0001; threat zone: t(9) = 7.604, p<0.0001; Wang et al, 2021b ).…”
Section: Resultsmentioning
confidence: 99%